FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KECEMASAN ORANG TUA ANAK PENDERITA KANKER - Sri Mardianti Anwar; Gamya Tri Utami; Nurul Huda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Cancer in children is a frightening condition for parents because not all of children can be able to survive and recover from this disease. The process of cancer and the duration of cancer treatment caused a great psychological impact for the sufferer and parents. This study aimed to determine the factors associated with the level of anxiety parents of children with cancer. The design of this study was descriptive correlation with cross-sectional design. The sample of this research is 73 respondents taken based on inclusion criteria using purposive sampling technique. Data analysis used univariate & bivariat by chi-square and kolmogrov-smirnov test. The result of univariate analysis was found that the majority of respondents were in the early adult age range (69.9%), male sex (43.8%), low education (49.3%), low income (64.4%), and experienced high levels of anxiety (53.4%). The result of bivariate analysis shows that the p value of each research variable is bigger than the value (α = 0,05) which can be concluded that there is no correlation between age (p value 0,055), gender (p value 0,669) , education (p value 0,995), and income (p value 0,938) with parental anxiety level. The results of this study indicate that parents experience high levels of anxiety, but trying to resolve the factors that can cause anxiety be able to focus on conditions of healing children.Keywords: Cancer, Cancer Factors, Anxiety Level